The Norms of National Law Forming the Basis for the Shaping and Implementing of State Policy in the Field of Energy Security. Discussion Based on the Polish Legal Order1 - Kamiński, Marcin (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2019)
The essential aim of the article is the theoretical analysis of the normative basis of the Polish state policy in the field of energy security. The analysis begins with the presen-tation of the state policy and energy policy concepts. The author argues that in the Polish legal order the concept of energy policy is concentrated around the premise of energy security. The next part of the analysis deals with the issues of categories of the norms shaping and implementing of the energy security policy in the Polish legal order. This part of the considerations shows that the normative basis for the determination, implementation and verification of political actions taken by the public authorities in the field of energy security requires the use of specific normative structures. The analysis refers to the conception of ‘goal-oriented norms’. The norms of this kind set binding goals, directions and conditions for the actions of state authorities as well in the field of energy policy. The types of the acts which concretize the goal-oriented norms (e.g. task-oriented norms; directional and determinative norms; planning norms) in the discussed field of state policy are also discussed.